Interplay between metabolic reprogramming and post-translational modifications: from glycolysis to lactylation - Wu, Hengwei; Huang, He; Zhao, Yanmin (Frontiers in Immunology, 2023)
Cellular metabolism plays a critical role in determining the fate and function of cells.Metabolic reprogramming and its byproducts have a complex impact on cellular activities. In quiescent T cells, oxidative phosphorylation (OXPHOS) is the primary pathway for survival. However, upon antigen activation, T cells undergo rapid metabolic reprogramming, characterized by an elevation in both glycolysis and OXPHOS. While both pathways are induced, the balance predominantly shifts towards glycolysis, enabling T cells to rapidly proliferate and enhance their functionality, representing the most distinctive signature during activation. Metabolic processes generate various small molecules resulting from enzyme-catalyzed reactions, which also modulate protein function and exert regulatory control. Notably, recent studies have revealed the direct modification of histones, known as lactylation, by lactate derived from glycolysis. This lactylation process influences gene transcription and adds a novel variable to the regulation of gene expression. Protein lactylation has been identified as an essential mechanism by which lactate exerts its diverse functions, contributing to crucial biological processes such as uterine remodeling, tumor proliferation, neural system regulation, and metabolic regulation. This review focuses on the metabolic reprogramming of T cells, explores the interplay between lactate and the immune system, highlights the impact of lactylation on cellular function, and elucidates the intersection of metabolic reprogramming and epigenetics.